Synergistic pathways between urbanization and low-carbon development: Evidence from the Yangtze River Economic Belt - Tong, Nian; Frazier, Amy E.; Tong, Luyi; Hu, Shougeng (Journal of environmental management, 2025)
Urbanization is the path to modernization, yet it also poses significant challenges to global climate change mitigation. The intricate interplay between urbanization and low-carbon development remains a subject of ongoing debate, highlighting the urgent need for synergistic solutions. Guided by a theoretical framework on urbanization and low-carbon development interactions, this study employs econometric and coupling coordination models to analyze the relationship and coordination performance between urbanization and carbon emission efficiency (CEE) in 110 cities at and above the prefecture level of the Yangtze River Economic Belt (YREB) from 2000 to 2020. Our findings reveal a promising win-win potential between urbanization and low-carbon development in the YREB, characterized by a mutually reinforcing relationship between urbanization and CEE, with heterogeneous interactions between different urbanization subsystems and CEE, as well as spatiotemporal variations in their synergistic effects. Specifically, land and social urbanization subsystems significantly enhanced CEE, while later-stages urbanization (2014–2020) had a more pronounced positive impact on CEE. Upstream and midstream regions continue to benefit from urbanization-driven CEE improvements, whereas downstream regions exhibit diminishing returns. Low-carbon pilot cities achieved higher CEE under government-led initiatives, while non-pilot cities relied more on self-driven urbanization processes. Notably, the feedback effects of CEE improvement on urbanization showed opposite heterogeneity. Over the past two decades, the coupling coordination between urbanization and low-carbon development has steadily improved, though a notable challenge emerged with urbanization development lagging behind low-carbon progress. These findings facilitate targeted efforts in advancing urban low-carbon transformation. •Systematic and spatiotemporal heterogeneity in urbanization-CEE interactions.•Land/social urbanization drives CEE more than population/economic urbanization.•Low-carbon pilot cities achieve higher CEE under government-led initiatives.•Upstream/midstream benefit more from urbanization-driven CEE than downstream.•Urbanization level lags behind CEE undermines their coordinated performance.